Embracing Transformation: Ethical Practices in Pedagogical Documentation - Kim, Bo Sun (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
This article explores pedagogical documentation as a situated and speculative practice in early childhood education. Drawing on philosophical concepts including Heidegger’s Dasein, Deleuze and Guattari’s becoming-minoritarian, and the idea of decentering the child, the paper examines how documentation shapes educators’ pedagogical thinking and relational ethics. Rather than focusing on how documentation shifts public views of early education, the article centers transformation as a lived, ethical, and pedagogical process. Through the Fishpond curriculum project, we attune to moments of pedagogical intra-action where documentation participates in the material-discursive reconfiguring of relations, generating speculative possibilities for thinking-with children, educators, and a pedagogist. The article positions documentation as a generative site of struggle that unsettles normative representational logics and sustains pedagogical matterings as ongoing processes of becoming.